Using Spiral Dynamic Algorithm for Maximizing Power Production of Wind Farm - Mok, Ren Hao; Raja Mohd Taufika, Raja Ismail; Mohd Ashraf, Ahmad (IEEE, 2017)
This paper presents a preliminary study of a model-free approach based on spiral dynamic algorithm (SDA) for maximizing wind farms power production. The SDA based approach is utilized to ﬁnd the optimal control parameter of each turbine to maximize the total power production of a wind farm. For simplicity, a single row wind farm model with turbulence interaction between turbines is used to validate the proposed approach. Simulation results demonstrate that the SDA based method produces higher total power production compared to the particle swarm optimization (PSO) and game theoretic (GT) based approaches.